African anthropologies : history, critique, and practice. - Ntarangwi, Mwenda; Mills, David; Babiker, Mustafa H. M. (Africa in the new millennium, 2006)
This landmark volume on the history, application and teaching of anthropology in post-colonial Africa shows how the continent’s anthropologists are redefining the historical legacy of European and American disciplinary hegemony, and developing distinctively African contributions to anthropological theory and practice. While illustrating the diverse national traditions of anthropological practice that have developed in sub-Saharan Africa since decolonisation, the contributors exemplify the diversity of professional work carried out by the discipline’s practitioners, united by their use of anthropological perspectives to make a difference. Their commitment to this disciplinary identity demonstrates the place that exists for a critical anthropology that is reflective about both its potentials and limitations.